Jamaluddin al-Afghani dan Karir Politiknya - Arbi Mulya Sirait (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
Abstract In its history, Islam has had a phase where it has progressed in various ways, one of which is in the political realm. This is marked by the number of areas that were successfully conquered by Islam so that its teachings also developed very rapidly. However, in history, Islam has also experienced a period of decline where there have been many divisions among internal Muslims as well as due to external influences, and some of the causes are the advancement of Western civilization so that it affects the existence of the world of Islamic politics as well. The data obtained from this paper comes from various references in the form of books, journals, and other writings. Then the data is reviewed to produce a conclusion. In this paper, we will discuss how Jamaluddin al-Afghani's efforts in arousing the spirit of unity of the Muslim community in order to escape from western influences and shadows, as well as his efforts to improve the internal conditions of Muslims, both social, political and religious. Jamaluddinal-Afghani the first reformer in Islam who brought salafiyah under the banner of Pan Islamism, with the principle that Muslims wherever he is is the Unity of Brothrhood or a unity of brotherhood that must be fostered continuously. Jamaluddin said that the only most revolutionary way to liberate the fate of Muslims from colonialism, imperialism and materialism was politics imbued with religion. Jamaluddin, as an Islamic reformer, tried hard to improve Islam from within by completely attacking superstition, khurafat and bid'ah. Key Word: Jamaluddin al-Afghani, Pan-Islamism, Political Islam